Immunity to Avian Leukosis Virus: Where Are We Now and What Should We Do? - Feng, Min; Zhang, Xiquan (Frontiers in Immunology, 2016)
Avian leukosis virus (ALV) is an avian oncogenic retrovirus causing enormous economic losses in the global poultry industry. Although ALV-related research has lasted for more than a century, there are no vaccines to protect chickens from ALV infection. The interaction between chickens and ALV remains not fully understood especially with regard to the host immunity. The current review provides an overview of our current knowledge of innate and adaptive immunity induced by ALV infection. More importantly, we have pointed out the unknown area involved in ALV-related studies, which is worthy of our serious exploring in future.